(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2012)
Does evolutionary theory have the potential to undermine morality? In his book The Evolution of Morality, Richard Joyce (2006) argues for a positive answer. He contends that an evolutionary account of morality would undermine moral judgements and lend support to moral scepticism. I offer a critique of Joyce’s argument. As it turns out, his case can be read in two different ways. It could be construed as an argument to establish a general scepticism about the justification of moral judgements. Or it could be read as an argument that targets only a particular meta-ethical position, namely moral realism. My claim is that it fails on both interpretations. There is no reason to believe that evolutionary considerations undermine morality.